2020
DOI: 10.1038/s41467-020-18456-y
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex flow magnetic tweezers reveal rare enzymatic events with single molecule precision

Abstract: The application of forces and torques on the single molecule level has transformed our understanding of the dynamic properties of biomolecules, but rare intermediates have remained difficult to characterize due to limited throughput. Here, we describe a method that provides a 100-fold improvement in the throughput of force spectroscopy measurements with topological control, which enables routine imaging of 50,000 single molecules and a 100 million reaction cycles in parallel. This improvement enables detection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 42 publications
3
42
0
Order By: Relevance
“…Using the magnetic tweezers single-molecule approach, we have not only demonstrated that M. mazei topo VI is a highly distributive and extremely slow supercoil relaxase, confirming findings from Wendorff et al, 2018 (38), but also shown that topo VI activity increases as much ~10-fold on braided DNA, (Figures 1, 2 and 4), approaching rates determined for type IIA topos on their respective optimal substrates (21,43,44). Along with the observation that topo VI has an extremely strict preference for DNA crossing geometries close to 90°, which appear more frequently in catenanes than they do in supercoils (21), these data strongly indicate that M. mazei topo VI is a preferential decatenase, which simultaneously disfavours supercoil relaxation.…”
Section: Mazei Topo VI Is a Chirally-selective Dna Crossing Sensorsupporting
confidence: 88%
See 2 more Smart Citations
“…Using the magnetic tweezers single-molecule approach, we have not only demonstrated that M. mazei topo VI is a highly distributive and extremely slow supercoil relaxase, confirming findings from Wendorff et al, 2018 (38), but also shown that topo VI activity increases as much ~10-fold on braided DNA, (Figures 1, 2 and 4), approaching rates determined for type IIA topos on their respective optimal substrates (21,43,44). Along with the observation that topo VI has an extremely strict preference for DNA crossing geometries close to 90°, which appear more frequently in catenanes than they do in supercoils (21), these data strongly indicate that M. mazei topo VI is a preferential decatenase, which simultaneously disfavours supercoil relaxation.…”
Section: Mazei Topo VI Is a Chirally-selective Dna Crossing Sensorsupporting
confidence: 88%
“…2 nM topo VI), the maximum rate measured for positive and negative supercoil relaxation was only 6.4 ± 0.6 and 3.5 ± 0.5 strand-passage events min -1 , respectively. As detailed in the subsequent section, these rates are 10-50-fold slower than rates measured for the type IIA topos, gyrase and topo IV (21,43,44). Wendorff et al (2018) found the maximal topo VI ATP hydrolysis rate, using the PK/LDH assay, to be ∼3 ATP min -1 during relaxation of negatively supercoiled plasmids (38).…”
Section: Topo VI Is a Slow Chirally-selective And Highly-distributivmentioning
confidence: 84%
See 1 more Smart Citation
“…The obtained standard deviations averaged at 32 nm for both x and y . This value corresponds to the experimental value of localization precision, the theoretical limit of the tracking precision in the used configuration was previously calculated to be 6 nm 26 .…”
Section: Methodssupporting
confidence: 74%
“…This also may damage the biological cell or specimen due to the heat generated by large incident power. 6,7 As the metal surface plasmon resonance structures with localized strong gradient electric elds can be used to optically trap nanoparticles, [8][9][10][11][12][13] many groups have focused on the optical trapping for a long time. [14][15][16] The optical force on the nanoparticles caused by the evanescent eld can draw the nanoparticles into a 'hot spot'.…”
Section: Introductionmentioning
confidence: 99%